Application of responsive nano-drug carriers in bone tumor chemotherapy - Peiyang Cai; Minjie Fan; Pengfei Zheng (Journal of Bone Oncology)
Bone tumors, especially malignant ones, have high mortality and disability rates, and traditional treatment methods have limitations. Responsive nano-drug carriers achieve targeted delivery and controlled release of drugs by precisely responding to the tumor microenvironment or external stimuli, thereby improving drug efficacy and reducing toxic side effects. These carriers, including liposomes, micelles, and nano-gels, can respond to internal stimuli such as pH, redox, enzymes, and hypoxia, as well as external stimuli such as light, magnetic fields, and ultrasound. By optimizing carrier design, significant improvements in drug targeting, bioavailability, and therapeutic effects can be achieved, providing new ideas and methods for the comprehensive treatment of bone tumors.